PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN ONLINE DI TOKOPEDIA PRODUK BAJU PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS ABDURACHMAN SALEH SITUBONDO DENGAN MINAT BELISEBAGAI VARIABEL MODERATING - Muhammad Holilur Rahman; Riska Ayu Pramesthi; Siti Soeliha (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to examine the effect of Service Quality and Price on Consumer Satisfaction through Online Purchase Decision, and to analyze the role of Purchase Intention as a moderating variable on the Tokopedia platform for clothing products among students of the Faculty of Economics at Abdurachman Saleh University Situbondo. This research is quantitative with an associative approach. Data were collected through questionnaires distributed to 88 student respondents who have purchased clothing online via Tokopedia. The data were analyzed using the Structural Equation Modeling (SEM) method with Partial Least Square (PLS) approach, assisted by SmartPLS 3.0 software. The results show that Service Quality and Price have a positive and significant effect on Online Purchase Decision and Consumer Satisfaction. Online Purchase Decision also significantly influences Consumer Satisfaction. Furthermore, Purchase Intention as a moderating variable strengthens the relationship between Online Purchase Decision and Consumer Satisfaction.